Prevalência e fatores associados à síndrome de burnout em enfermeiros intensivistas em uma cidade da Bahia - Aragão, Núbia Samara Caribé (2019)
Burnout syndrome is a chronic reaction to the excessive and exhausting relationship with people in the work environment, considered as having a multifactorial etiology, a kind of coping and self-protection in the face of the stress generated in interpersonal relationships. The work of nurses working in the Intensive Care Unit is considered to be exhaustive, requiring, in addition to qualified technical knowledge, skills, attention, fast reasoning and emotional balance to deal with the adversities that arise in their daily work, in the face of living with patients and coworkers. Objective: To estimate the prevalence and factors associated with burnout syndrome in intensive care nurses in a city in the state of Bahia. Method: This research results from data from a matrix project entitled "Mental health of intensive care workers from a large city in Bahia". Data collection was performed from August to November 2016. To know what has been produced in Brazil and the world on Burnout Syndrome in intensive care nurses, a systematic review was initially conducted. Subsequently, a cross-sectional study was carried out to evaluate the prevalence and factors associated with burnout syndrome in intensive care nurses in a city in the state of Bahia, Brazil, with 65 individuals. The application of a questionnaire was performed to obtain socioeconomic-demographic information, life habits, related to health. The instrument used was composed of questions about: the sociodemographic profile of the interviewees; general information about ICU work; workplace; psychosocial aspects of the work, using the Job Content Questionnaire (JCQ); habits of life and assessed the mental health of workers using the Maslach Burnout Inventory (MBI) for the suspicion of Burnout Syndrome. The prevalence ratios (PR) and respective 95% confidence intervals (95% CI) were obtained by association analysis. Results: The findings were presented as an article. Article 1 - 13 articles published between the years 2007 to 2018 were selected. The high prevalence of the burnout syndrome was the most observed result and the variables most associated with the syndrome were; age, sex, marital status, time and work shift. In article 2, there was a high prevalence of Burnout Syndrome (53.6%) associated with age, smoking, use of alcoholic beverages, work hours at night, work relationship, specialist degree in Intensive Care, number of patients attended per shift, monthly income and consider active work or high demand. Conclusions: It was observed a high prevalence of Burnout Syndrome associated mainly to factors related to work and life habits in intensive care nurses of a city in the state of Bahia. These findings can contribute to decision making related to improvements in working conditions and also to the awareness of managers and workers about how interpersonal and organizational relationships at work can contribute to workers' mental